Karateristik Pendidikan Inter-Religius Dalam Al-qur’an - Muhammad Hariyadi; Imronuddin Imronuddin (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
The conclusion of this article is that inter-religious education in the Quran is an education that encourages all students to have an intellectual, moral, achievement and noble personality with humanity and togetherness orientation to develop the principles of democracy, equality and justice in social life and compassion for the universe on the basis of faith in God. Students are required to know the background of each religion and not see it from just one perspective, but also through the perspectives of others to avoid excessive fanaticism in religion that can be a trigger for conflict so far. The article also found two things needed in the construction of Inter-Religious Education, namely; firs! to carry out dialogue by placing each religion in an equal position. Second, develop an attitude of tolerance by providiug opportunities for each religion to urderstand each other. The method that authors use in this study is a qualitative method that is supported by research libraries. While the method of interpretation that authors use is the method of interpretation maudu'i, the authors chose this method because this method can be used as an excavator of lnter-Religious Education according to the Qur'an more comprehensively.